Tax incentive, R&D manipulation and enterprises' innovation performance: the moderating role of political connections. (3rd January 2023) - Xiong, Ran; Wei, Ping; Yang, Jingyi; Cristofini, Luis Antonio
Mainland China has a tax incentive named the policy of recognising HTEs that provides a 15% preferential tax rate to enterprises whose investment in R&D exceeds a given notch. We evaluate how recognising HTEs affects enterprises' innovation performance and explore the moderating role of political connections and R&D manipulation. Results show that the recognition of HTEs relates positively to enterprises' innovation performance but that political connections negatively moderate the relationship between recognising HTEs and enterprises' innovation performance. However, the moderating effect exists only in regions with more government intervention, less financial development, and less protection for intellectual property. Further analysis shows that political connections significantly increase enterprises' efforts to manipulate reports of their R&D expenses, and such manipulation weakens the relationship between their R&D investment and output. Our conclusions provide evidence of the distortion created by this tax incentive, and they offer a theoretical reference for improving the policy of recognising HTEs.